The Impact of Various Diets on the Management of Patients with Type 1 Diabetes - systematic review - Mateusz Kacalak (Quality in Sport, 2025)
Introduction: Type 1 diabetes (T1D) is a chronic autoimmune disorder characterized by the destruction of pancreatic β-cells, leading to absolute insulin deficiency. Given the increasing global incidence—especially among children and adolescents—growing attention is being paid not only to pharmacological treatment but also to the supportive role of targeted nutritional interventions.